PENGARUH MOTIVASI, LINGKUNGAN KERJA DAN NILAI SOSIAL TERHADAP MINAT MAHASISWA AKUNTANSI DALAM MEMILIH KARIR SEBAGAI AKUNTAN PUBLIK - Senjari, Richa; Hasan, Amir; Sofyan, Azhari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aimed to examine the effect of motivation, work environment and social values on accountant students interest for choosing the profession as a public accountant.The research was conducted by taking a sample of 95 people from the Faculty of Economics from Riau University, National Islamic University and Riau Islamic University, class of 2009 to 2011, sampling was based on a purposive sampling method. Data from this study are then processed using multiple regression analysis through SPSS 17 statistical applications.Results of this study indicate that the economic motivationssignificantly affect accountant students interest in career choice as a public accountant. While variable labor market motivation, work environment and social values do not significantly influence the selection of a career as public accountants by accounting students. Coefficient of determination (R2) in this study was 0.115. This suggests that the effect of the independent variable on the dependent 11.50% and the remaining 88.50% is influenced by other variables.Keywords: Economic Motivation, Labour Market Motivation, Work Environment, social values and interest.